EXEMPLARY MODEL OF GOOGLE TRANSLATE UTILIZATION IN ENHANCING ARABIC LANGUAGE ACQUISITION AMONG MALAY LEARNERS - Dr. Muhamadul Bakir Hj. Yaakub, (Journal of Islamic, Social, Economics and Development, 2021)
This article focuses on introducing an exemplary model for Malay learners of Arabiclanguage in using Google Translate to fulfil their language needs and necessities which isregarded as a natural social reaction within multi-racial societies, especially in the occasionof problem-solving and self-regulated learning strategies. This exploratory study wasprompted by the question â€œDoes using Google translate fulfil my language needs?â€ when usedaccording to its guidelines, students improve their language acquisition and capability totranslate texts with fewer syntactic and semantic errors. The model was develop based onLeonardiâ€™s (2011) call for a re-evaluation and a rehabilitation of the translation activities intheir foreign language classes. The findings also show that there are various forms oftranslation mistakes and difficulties confronted by Malay learners of Arabic language. Itâ€™scaused by ineffective usage of the software for the purpose of second language acquisition.This study proposes an exemplary model of application procedures and analysis of machinetranslation output based on identification of its semantics and pragmatics aspects. For thisstudy, the proposed model was tested with small sampling in an unofficial classroom and is yetto be tested within a comprehensive official classroom in the future research. As per the mainobjective, which is addressing student awareness of Google Translate shortcomings anddisadvantages. Therein, they will become more responsible and critical in nature to search forsupports and solutions. Consequently, more empirical data will be needed for this achievement.Obviously, the issue of this study is very much timely, especially in term of teacher-studentengagement in analyzing linguistics features of language usage.